Gambaran Pengetahuan, Sikap, dan Praktik Pencegahan COVID-19 pada Penderita Hipertensi - Amalia, Hilda; Pratomo, Hadi (UI Scholars Hub, 2022)
Background. Depok City is the highest city with the number of confirmed COVID-19 (49.567 cases) and cumulative deaths (920 deaths) in West Java on 30 Mei 2021. Hypertension patients must be more disciplined in COVID-19 prevention because they are more likely to experience severe COVID-19 disease development. Objective. This study aims to describe the knowledge, attitude, and practice of COVID-19 prevention among hypertension patients in Depok City. Method. This study used a cross-sectional study of hypertension patients in Depok City, West Java, from August to September 2021. Data collected used an online survey (google form). Results. The results showed the mean knowledge score on a scale of 100 was 85,2, the attitude was 77,7, and practice was 82,4. Half of the respondents had good knowledge (52,5%), a positive attitude (63,9%), and good practice (58,5%). The results of the relationship analysis for knowledge and practice of COVID-19 prevention obtained a p-value of 0.681, and attitudes toward COVID-19 prevention practices obtained a p-value of 0.011. Conclusion. There is no significant relationship between knowledge and COVID-19 prevention practices. There is a significant relationship between attitudes and COVID-19 prevention practices.